Factors affecting the initiation and continuation of maternal health service utilization among women who delivered in the past one year in Enemay district, East Gojjam, Ethiopia - Anguach Shitie; Zelalem Nigussie Azene (BMC, 2021)
Abstract Background Maternity continuum of care is the continuity of maternal healthcare services that a woman uses, which includes antenatal care (ANC 4+), skilled birth attendant (SBA), and postnatal care (PNC) within 48 h of delivery. It is one of the essential strategies for reducing maternal and newborn morbidity and mortality. Therefore, this study aimed to assess the prevalence and factors affecting the initiation and continuation of maternal health service utilization among women who delivered in the past one year in Enemay district, East Gojjam zone, Ethiopia. Methods A community-based cross-sectional study was conducted among six hundred twenty-one (621) women who gave birth in the last one year in Enemay district from February 25 to March 10, 2019. A simple random sampling technique was used to select the study participants. Data were collected by face-to-face interviewer-administered, pretested, and semi-structured questionnaire. Binary logistic regressions (bi-variable and multivariable) were fitted to identify statistically significant variables. Adjusted Odds Ratio (AOR) with 95% Confidence Interval (CI) was used to declare statistically significant variables on the basis of p-value < 0.05 in the multivariable binary logistic regression. Results In this study, around 61% of women had antenatal care follow-up. Out of those women having ante natal care follow-up, about 77.5% (95% CI 73, 81.7%) had continued to receiving skilled birth delivery service. Age (AOR = 1.7 95% CI: (1.0, 2.88)), marital status (AOR = 1.6, 95% CI: (1.01, 2.76)), women's educational status (AOR = 2.9, 95% CI: (1.30, 6.72)), autonomy for health care decision-making (AOR = 3.71, 95%CI: (2.36, 6.02)), exposure to media (AOR = 2.8, 95% CI: (1.78, 4.6)), wanted pregnancy (AOR = 3.6 95% CI: (2.2, 5.95)), and parity (AOR = 0.34, 95%CI: (0.16, 0.71)) were statistically significant variables associated with initiation of antenatal care, whereas educational status of women (AOR = 4.65, 95% CI: (1.37, 15.7)), autonomy for health care decision making (AOR = 2.62, 95% CI:(1.0, 6.82)), and had counseled during antenatal care (AOR = 2.88 95% CI: (1.21, 6.83)) were statistically significant variables associated with the continuation of maternal health care services. Conclusions This study demonstrated that the initiation and continuity of maternal health care services are low in the study area. Age, marital status, residence, women's educational status, health care decision-making autonomy, exposure to media, wanted pregnancy, and parity were factors significantly affecting the initiation of antenatal care. Whereas, women's educational status, health care decision-making autonomy, and counseling during antenatal care were predictors influencing the continuation of maternal health care services (antenatal care to skilled birth delivery).